A novel approach for fine-grained traffic risk characterization and evaluation of urban road intersections. (March 2023) - Yang, Lin; Luo, Xuekun; Zuo, Zejun; Zhou, Shunping; Huang, Tianyou; Luo, Shan
Highlights: A risk diffusion model integrating motion mechanism is proposed. It characterizes the full field distribution of traffic risks at urban road intersections. The multi-dimensional hierarchical evaluation index system for traffic risks at intersections is established. It provides a variety of quantitative tools to implement multiple-granularity traffic risk evaluation. Abstract: An urban road intersection environment with low traffic risk is an essential component of sustainable cities. Various risk analysis and simulation techniques have been developed to measure and evaluate traffic risks. However, flexible assessment of intersection risk at a fine resolution remains a great challenge. This study proposes a novel approach for characterizing the field distribution of traffic risks at an urban road intersection and assessing traffic risks in multiple dimensions to increase the flexibility of risk assessment. First, we define a new traffic risk metric to quantify the risk of intersection traffic conflict points by combining their frequency and severity. Second, the plume diffusion model is introduced to model the non-linear relationship between traffic conflict points by considering the propagation of the traffic risk in the intersection. In this way, the entire intersection risk distribution map is derived for real-time risk analysis. Finally, a multidimensional hierarchical evaluation system of traffic risk at intersections is designed, including the traffic risk indicators at the intersection, path, and turn mode levels. The results of a case study in Wuhan, China, demonstrate the continuous characterization results of the risk field and provide multidimensional risk assessment index results, which are highly consistent with the cognitive results of manual risk scoring (up to 90% similarity). It also allows for risk assessment in a single path and turn modes through the risk field characterization and reveals the spatiotemporal dynamic risk distribution, thus providing an alternative tool for risk decision-making at urban road intersections.